CRITICAL FACTORS AFFECTING LOADING AND UNLOADING PERFORMANCE AT PORT TERMINALS: Faktor-Faktor Kritis Yang Mempengaruhi Kinerja Bongkar Muat Di Terminal Pelabuhan - fandi ahmad; Galih Satriyo; Suwarso (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Ports play a strategic role in global trade as key gateways in international supply chain flows, yet they often become bottlenecks when operational capacity fails to meet increasing cargo volumes. This study investigates the critical factors influencing cargo handling performance at port terminals using a Systematic Literature Review (SLR) approach to synthesize findings from reputable scholarly databases published between 2015 and 2024. The review identifies four dominant determinants: infrastructure and equipment, human resources (HR) capability, information technology adoption, and operational management systems. Results show that ports with adequate quay cranes, sufficient berth capacity, and compatible water depth achieve higher Box per Hour (BPH) and Ton per Hour (TPH) productivity. HR competency, particularly among stevedores, also strongly influences operational speed and safety, highlighting the importance of upskilling and technology-oriented training. Furthermore, integrated Terminal Operating Systems (TOS), digital documentation, and real-time tracking significantly reduce waiting times and administrative errors, although digitalization gaps remain evident in developing countries. Effective operational management—such as vessel scheduling, queue control, and safety governance—further enhances overall productivity and reduces turnaround time. The findings reveal strong interdependence among all four factors, confirming that cargo handling performance is system-dependent rather than isolated. Research gaps emerge in the areas of behavioral HR studies, multi-agency collaborative governance, and the integration of data analytics into port operations. This study provides a comprehensive framework to guide policymakers and port operators in formulating holistic strategies to improve terminal efficiency and strengthen national logistics competitiveness.